Hubungan Persepsi Ibu Hamil Tentang Mutu Pelayanan Antenatal dengan Minat Kunjungan Ulang di Puskesmas Tlogosari Kulon Kota Semarang - Rizki Pamulat Sari; Septo Pawelas Arso; Putri Asmita Wigati (Jurnal Kesehatan Masyarakat (Undip), 2017)
The coverage of antenatal care at TlogosariKulon Health Center has not reached the target and the number of visit is decrease.The decrease caused by the disinterest of some pregnant women on antenatal services that were felt to take a long time, the number of waiting room is less, and the officers are less thorough when checking. The quality of antenatal care in this terms of 5 dimensions that is reliability, responsiveness, assurance, empathy, and tangible. The purpose of this study was to find out the correlation between the quality of integrated antenatal care with the interest of repeat visit. The method of this research was using explanatory research with cross sectional approach. The total population of 218 people with sample 68 was calculated using the slovin formula. Data analysis using univariate and bivariate with a chi-square test. The results showed that the perception of reliability was not relates to the interest of repeat visit of antenatal service (p-value = 0,091). The perceptions of responsiveness relates to interest in repeat visits of antenatal  service (p-value = 0,000). The perception of assurance relates to the interest of repeat visits of antenatal service (p-value = 0.001). The perceptions of emphaty relates to interest in repeat visits of antenatal service (p-value = 0,000). The perceptions of tangible relates to interest in repeat visits of antenatal service (p-value = 0,000). The perceptions of the quality of integrated antenatal care relates to the interest in repeat visits (p-value = 0,000). Based on the results of research, it is necessary to increase the speed of service, detailed information in the examination,extension waiting room facilities in the public health center, and renewal of tools that are not feasible to use.